Petrophysical, Geochemical, and Hydrological Evidence for Extensive Fracture‐Mediated Fluid and Heat Transport in the Alpine Fault's Hanging‐Wall Damage Zone. (29th December 2017) - Townend, John; Sutherland, Rupert; Toy, Virginia G.; Doan, Mai‐Linh; Célérier, Bernard; Massiot, Cécile; Coussens, Jamie; Jeppson, Tamara; Janku‐Capova, Lucie; Remaud, Léa; Upton, Phaedra; Schmitt, Douglas R.; et al.
Abstract: Fault rock assemblages reflect interaction between deformation, stress, temperature, fluid, and chemical regimes on distinct spatial and temporal scales at various positions in the crust. Here we interpret measurements made in the hanging‐wall of the Alpine Fault during the second stage of the Deep Fault Drilling Project (DFDP‐2). We present observational evidence for extensive fracturing and high hanging‐wall hydraulic conductivity (∼10 −9 to 10 −7 m/s, corresponding to permeability of ∼10 −16 to 10 −14 m 2 ) extending several hundred meters from the fault's principal slip zone. Mud losses, gas chemistry anomalies, and petrophysical data indicate that a subset of fractures intersected by the borehole are capable of transmitting fluid volumes of several cubic meters on time scales of hours. DFDP‐2 observations and other data suggest that this hydrogeologically active portion of the fault zone in the hanging‐wall is several kilometers wide in the uppermost crust. This finding is consistent with numerical models of earthquake rupture and off‐fault damage. We conclude that the mechanically and hydrogeologically active part of the Alpine Fault is a more dynamic and extensive feature than commonly described in models based on exhumed faults. We propose that the hydrogeologically active damage zone of the Alpine Fault and other large active faults in areas of high topographic relief can be subdivided into an inner zone in which damage is controlled principally by earthquake rupture processes and an outer zone in which damage reflects coseismic shaking, strain accumulation and release on interseismic timescales, and inherited fracturing related to exhumation. Plain Language Summary: The Alpine Fault produces large (magnitude ~8) earthquakes approximately every 300 years and last ruptured 300 years ago in 1717 AD. Understanding the state of the fault — the temperatures, pressures, stresses to which the fault is being subjected — ahead of an anticipated large earthquake is an important scientific challenge and the focus of the Deep Fault Drilling Project. In this paper, we report findings from scientific drilling in 2014 that reveal evidence for active fluid flow adjacent to the Alpine Fault. The transport of heat and mass near the fault appears to be controlled or modulated by earthquake shaking and rupture processes, and likely controls the build‐up of pressure and stress in the shallow portions of the crust during the ~300 year earthquake cycle. Key Points: DFDP‐2B data to 818 m true vertical depth reveal extensive fracturing of the Alpine Fault hanging‐wall and high hydraulic conductivity The effective hydrogeological width of the damage zone exceeds the width implied by fracture density by at least an order of magnitude In areas of high relief and rapid slip, damage is controlled by coseismic, interseismic, and inherited deformation modulated by topography